"Unknown Symbols": Online Legal Research in the Age of Emoji. Issue 4 (2nd October 2019) - Behrens, Jennifer L.
Abstract: Over the last decade, emoji and emoticons have made the leap from text messaging and social media to legal filings, court opinions, and law review articles. However, emoji and emoticons' growth in popularity has tested the capability of online legal research systems to properly display and retrieve them in search results, posing challenges for future researchers of primary and secondary sources. This article examines current display practices on several of the most popular online legal research services (including Westlaw Edge, Lexis Advance, Bloomberg Law, Fastcase, HeinOnline, and Gale OneFile LegalTrac) and suggests effective workarounds for researchers.